Foreign entry strategies: strategic adaptation to various facets of the institutional environment - Ferreira, Manuel Portugal (2007)
In this paper we develop a comprehensive model of MNEs' foreign entry strategies and theorize how and how much the entry strategy is likely to be determined in the interface between internal and external pressures for both conformity and legitimacy. We develop an adaptation argument, in contrast to a selection rationale, through which we enhance our understanding of the various facets of the institutional environment and the constraints international managers encounter in their internationalization strategies.